Significance of Deha-Prakriti (Physic-Physiological Constitution) And Manasa-Prakriti (Psychological Constitution) In Vyadhyutpatti (Manifestation of Disease) - An Appraisal: Life Sciences -Ayurveda - Khaire, Utkarsha; Joshi, Dnyanesh; Borkar, Preeti; Chinthala, Rajkumar; Mhaiskar, Bhushan; Yadav, Deepak (International Journal of Life Science and Pharma Research, 2023)
Prakriti helps as a diagnostic tool for Disease, management, and treatment of Disease. Prakriti also helps in balancing the health of healthy persons. According to the Principles, all body functions depend on the Prakriti. Sharir and Manas Prakriti have an important role in Hetu(Cause), Linga(Symptoms), and Aushadha Skandha(Medicine). Vyadhi(Disease) is the opposite health condition; according to Shabdakalpadrum, "Vyadh" means ’Pain.’Adding the ’Ikarant’ in Vyadh means "conglomeration of the pain." According to the Tridosha Siddhanta of the Ayurveda, Vata Pitta and Kapha Doshas are responsible for the Prakriti formation, as an imbalance in Doshas leads to diseases; therefore, knowledge of Prakriti of an individual is essential for the knowledge of Vikriti. With the knowledge of an individual’s Prakriti, it is possible to apply fundamental Ayurvedic principles in the promotion of health prevention as well as the management of diseases in a successful manner. Prakriti has a very important role in healthy and unhealthy people. The Main cause of the Disease is not following a proper lifestyle and regular intake of an imbalanced diet. Knowledge of Prakriti should be utilized in the diagnosis, treatment, and maintenance of the health of a healthy individual. By applying the concept of Prakriti, various diseases can be treated and prevented efficiently. Our aim and objective of the study is to study the concept of Prakriti in the context of Vyadhi and to establish the interrelationship between Prakriti and Vyadhi. Ayurveda has provided detailed guidelines in the frame of dinacharya and rutucharya to maintain the normal functioning of Dosha related to specific Prakriti. Knowing about one Prakriti, we can select what benefits the individual. Thus Prakriti has an important role in dealing with health problems and prevention of diseases.